Tasting is knowing: the aesthetics and politics of disgust in John Layman's and Rob Guillory's Chew. Issue 1 (2nd January 2019) - Roan, Jeanette
ABSTRACT: Chew, written by John Layman and drawn by Rob Guillory, is a disgusting comic. Yet that is precisely its appeal. This article begins with the paradox of aversion, a question drawn from the realm of aesthetic theory, to ask why readers made a bestseller of this comic about a cannibal cop. A close textual analysis of Chew shows how Layman and Guillory use the possibilities and constraints of the medium of comics, along with a substantial infusion of humour, to skilfully deploy the simultaneous attraction and repulsion inherent in disgust. The article then argues that the comic effectively challenges the functions of moral disgust. Chew implicitly undermines the racist discourses associated with Asians and food in the West, and it suggests that cannibalism can serve as an acceptable manner of gaining information and of communing with the dead. Chew 's balance between the visceral repulsion and fascination of the disgusting, its humorous play at the borders of cultural transgression, and the narrative necessity of disgusting actions results in a meaningful and highly entertaining engagement with the aesthetics and politics of disgust that redraws the boundaries of what is fit for human consumption.